If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying P + -167 = 321 Reorder the terms: -167 + P = 321 Solving -167 + P = 321 Solving for variable 'P'. Move all terms containing P to the left, all other terms to the right. Add '167' to each side of the equation. -167 + 167 + P = 321 + 167 Combine like terms: -167 + 167 = 0 0 + P = 321 + 167 P = 321 + 167 Combine like terms: 321 + 167 = 488 P = 488 Simplifying P = 488
| 180=j-24 | | 125-2x=5x+20 | | -0.875m=0.25 | | 1.7u=0.2 | | =x^2-5x-6 | | K-32=217 | | 0.75y=-0.5 | | 4p+14=11p | | 0.25x+5=9 | | 150+y=879 | | -3=0.4v | | 91=x+52 | | -3=0.4 | | x=(x+1)(x+y) | | 5=0.6w | | 7x+38=-5x-10 | | W+233=319 | | -1.5d=8 | | D-67=23 | | 840=45+f | | y^2-5= | | 314+z=350 | | 0.6x=-4 | | 0.7y=12 | | 12z-12-4z=6-2z+32 | | (x^2-1)(x^2+2x+1)= | | 3x^5y^3+81x^5= | | 5y^2-5= | | -3x^2(4x^2-3x+3)= | | y^2-4y-5= | | y-8=15 | | -(6y-5)-(-5+4)=3 |